ANALISIS FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN STATUS GIZI PADA BALITA DI PUSTU BURAEN WILAYAH KERJA PUSKESMAS SONRAEN KABUPATEN KUPANG - Ardi oematan; Yohanes Dion; Arman Rifat Lette (CHMK HEALTH JOURNAL, 2021)
Toddler health is still a national problem which needs to be given top priority because it really determines the quality of human resources. The purpose of this study is to determine the factors associated with nutritional status in children under five in the Buraen Sub-district Work Area of ​​the Sonraen Health Center in Kupang Regency. This type of research was analytic descriptive with cross sectional approach. The sampling technique used in this study was purposive sampling. The sample in this study amounted to 112 people who were obtained using purposive sampling techniques in accordance with specified inclusion criteria. The results showed that dietary factors were 57 (50.9%), socio-cultural 106 (94.6%), infectious diseases 83 (74.1%), health services 112 (100%), nutritional status 105 (93.8%). Chi square test results showed that there was a significant relationship between infectious diseases and nutritional status in infants in Pustu Buraen with p-value = 0.028 where р <α (α = 0.05), there is no relationship between eating patterns, social culture and health services with the nutritional status of children under five where р> α (α = 0.05). Advice for parents of toddlers to be able to preach their children so they avoid infectious diseases and health woerkes to continue to improve education efforts on prevention of infectious diseases. Health workers can also increase efforts to improve the nutritional status of children under five such as : home visits, monitoring and ensuring the provision of supplementary food. Keywords: Related Factors, Nutritional Status, Toddler